2016
DOI: 10.1016/j.stemcr.2016.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Human Fibroblasts to Stably Self-Renewing Neural Stem Cells with a Single Zinc-Finger Transcription Factor

Abstract: SummaryDirect conversion of somatic cells into neural stem cells (NSCs) by defined factors holds great promise for mechanistic studies, drug screening, and potential cell therapies for different neurodegenerative diseases. Here, we report that a single zinc-finger transcription factor, Zfp521, is sufficient for direct conversion of human fibroblasts into long-term self-renewable and multipotent NSCs. In vitro, Zfp521-induced NSCs maintained their characteristics in the absence of exogenous factor expression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 34 publications
1
60
0
Order By: Relevance
“…A key question to assess the outcome of direct conversion strategies is to which extent directly converted iNSCs recapitulate these characteristics [11,71]. In order to demonstrate selfrenewal potential and clonal growth ability, iNSCs were either cultivated as primary and secondary neurospheres [33,34], analyzed in colony formation assays [28,33,36,39,42,48,72], and/or passaged several times [11,13,14,26,30,32,33,38,57,59,60,73]. On the other hand, all iNSC populations have been reported to express pan-neural markers, to be at least bipotential, and to show self-renewal and clonal growth ( Table 2).…”
Section: Molecular and Cellular Characterization Of Inscsmentioning
confidence: 99%
See 4 more Smart Citations
“…A key question to assess the outcome of direct conversion strategies is to which extent directly converted iNSCs recapitulate these characteristics [11,71]. In order to demonstrate selfrenewal potential and clonal growth ability, iNSCs were either cultivated as primary and secondary neurospheres [33,34], analyzed in colony formation assays [28,33,36,39,42,48,72], and/or passaged several times [11,13,14,26,30,32,33,38,57,59,60,73]. On the other hand, all iNSC populations have been reported to express pan-neural markers, to be at least bipotential, and to show self-renewal and clonal growth ( Table 2).…”
Section: Molecular and Cellular Characterization Of Inscsmentioning
confidence: 99%
“…As a matter of fact, the various protocols for the generation of iNSCs give rise to distinct iNSC populations that slightly differ in self renewal capacity, marker expression, and regional identity, as well as in vitro and in vivo differentiation potential. While Kim et al [11] reported passage of their mouse iNSCs for 3-5 times only, more recent studies demonstrated maintenance of NSC characteristics for more than 30 passages [13,14,28,34,36,38,58,73]. In order to demonstrate selfrenewal potential and clonal growth ability, iNSCs were either cultivated as primary and secondary neurospheres [33,34], analyzed in colony formation assays [28,33,36,39,42,48,72], and/or passaged several times [11,13,14,26,30,32,33,38,57,59,60,73].…”
Section: Molecular and Cellular Characterization Of Inscsmentioning
confidence: 99%
See 3 more Smart Citations